Disease Profile and Death Pattern Among Children Admitted in a Medical College Hospital - Hasan, M Shameem; Barua, Sanat Kumar; Mahmud, M Nasiruddin; Kamal, AHM; Enayetullah, M; Karim, M Rezaul (Bangladesh Journal of Child Health, 2012)
Background: An understanding of epidemiological trend in hospital admissions, including diseases and death pattern, is critical for health care planning, appropriate resource allocation & improving existing services facilities. Objectives: To evaluate the disease and death pattern of children admitted in the department of Child Health, Chittagong Medical College Hospital (CMCH), Chittagong. Materials and Methods: This was a retrospective study. The case records of all patients admitted in the department from Jan 1, 2008 to Dec 31, 2010 were analyzed. Result: Total 38,692 children were admitted during this study period; among them total 1897(4.9%) patient died. Infant and under five age groups constitute 45.2% and 75.9% respectively, total admission whereas deaths from the same groups were 43.7% & 79.3% respectively. Bronchopneumonia (22%), acute watery diarrhea (15%), hereditary hemolytic anemia (12%), and bronchiolitis (10%), topped the first four positions in each of the three years of admission. Septicemia and encephalitis, with a case fatality rate of 24% and 35% respectively, were found as top two causes of death. Highest case fatality rate was found in hepatic encephalopathy (54%). Other common causes of death include meningitis (19%), severe malaria (21%), leukemia (22%), severe malnutrition with complications (11%), and congenital heart diseases (12%) Conclusion: Comprehensive evaluation of admission and death related findings of this study will help to determine possible gaps in patient care and planning for more effective case-management strategies. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13081 Bangladesh J Child Health 2012; VOL 36 (2) : 66-70